All-solid-state sodium ion secondary battery
By using a solid electrolyte layer of sodium ion conductive oxide and a third electrode that can release sodium ions in an all-solid sodium ion secondary battery, the problems of low first charge and discharge efficiency and poor cycle characteristics are solved, and higher charge and discharge efficiency and capacity are achieved.
Patent Information
- Application Number
- CN202380064155.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-22
- Filing Date
- 2023-12-19
- Publication Date
- 2025-04-18
AI Technical Summary
The rocking chair-type all-solid sodium ion secondary battery has problems such as low first charge and discharge efficiency and poor cycle characteristics during repeated charge and discharge.
A solid electrolyte layer containing a sodium ion conductive oxide is adopted, and a third electrode is provided between the positive electrode and the negative electrode layer, which is composed of a metal capable of releasing sodium ions for replenishing sodium ions.
The first charging and discharging efficiency is improved, and the battery capacity is enhanced after repeated charging and discharging, the irreversible capacity is reduced, and the degraded state of the battery can be diagnosed and restored.
Smart Images

Figure CN119856317A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an all-solid-state sodium ion secondary battery. Background Art
[0002] Lithium ion secondary batteries have established their position as high-capacity and lightweight power sources that are indispensable for mobile devices, electric vehicles, etc. However, in existing lithium ion secondary batteries, flammable organic electrolytes are mainly used as electrolytes, so there is a concern about the danger of fire. As a method to solve this problem, people are promoting the development of all-solid-state batteries such as all-solid-state lithium ion batteries that use solid electrolytes to replace organic electrolytes. However, there are problems with low ion conductivity, difficulty in low-temperature operation and high output in oxide-based solid electrolytes with lithium ion conductivity. Therefore, as a substitute, people are promoting the development of all-solid-state sodium ion secondary batteries (for example, patent document 1) using oxide-based solid electrolytes with sodium ion conductivity.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2010-15782. Summary of the invention
[0006] Problem that the invention aims to solve
[0007] As an all-solid-state sodium ion secondary battery, a rocking chair type battery is known in which a material containing sodium ions as carrier ions is used as a positive electrode active material and a material containing no sodium ions is used as a negative electrode active material.
[0008] However, the rocking-chair-type all-solid-state sodium-ion secondary battery has problems such as poor initial charge and discharge efficiency and insufficient cycle characteristics during repeated charge and discharge.
[0009] The object of the present invention is to provide an all-solid-state sodium ion secondary battery capable of improving the initial charge and discharge efficiency and the capacity after repeated charge and discharge.
[0010] Technical means of solving problems
[0011] Various methods of all-solid-state sodium ion secondary batteries that solve the above-mentioned problems will be described.
[0012] The all-solid-state sodium ion secondary battery of embodiment 1 of the present invention is characterized in that it includes: a solid electrolyte layer, which has a first main surface and a second main surface relative to each other and is composed of a sodium ion conductive oxide; a positive electrode layer, which is arranged on the first main surface of the solid electrolyte layer; a negative electrode layer, which is arranged on the second main surface of the solid electrolyte layer; and a third electrode, which is connected to the solid electrolyte layer and contains a metal capable of releasing sodium ions.
[0013] The all-solid-state sodium ion secondary battery of Embodiment 2 is preferably such that, in Embodiment 1, the third electrode is an electrode for replenishing sodium ions.
[0014] The all-solid-state sodium ion secondary battery of Embodiment 3 is preferably such that, in Embodiment 1 or Embodiment 2, the third electrode is made of metallic sodium.
[0015] The all-solid-state sodium ion secondary battery of embodiment 4 is preferably such that, in embodiment 1 or embodiment 2, the third electrode is composed of an alloy containing at least one metal selected from the group consisting of Sn, Ti, Bi, Au, Al, Cu, Sb and Pb and metallic sodium.
[0016] The all-solid-state sodium-ion secondary battery of mode 5 is preferably that, in any one of modes 1 to 4, the positive electrode layer is in contact with the solid electrolyte layer, the projected area of the positive electrode layer located on the solid electrolyte layer when viewed from the stacking direction is smaller than the projected area of the solid electrolyte layer, and the third electrode is provided on a portion of the first main surface of the solid electrolyte layer that is not in contact with the positive electrode layer.
[0017] The all-solid-state sodium-ion secondary battery of mode 6 is preferably that, in any one of modes 1 to 5, the solid electrolyte layer is in contact with the negative electrode layer, the projected area of the negative electrode layer located on the solid electrolyte layer when viewed from the stacking direction is smaller than the projected area of the solid electrolyte layer, and the third electrode is provided on a portion of the second main surface of the solid electrolyte layer that is not in contact with the negative electrode layer.
[0018] The all-solid-state sodium ion secondary battery of aspect 7 is preferably such that, in any one of aspects 1 to 6, the surface layer of the solid electrolyte layer is a porous layer, and the third electrode is connected to the porous layer.
[0019] The all-solid-state sodium-ion secondary battery of mode 8 is preferably that, in any one of modes 1 to 7, the solid electrolyte layer has a first solid electrolyte layer as a dense layer and a second solid electrolyte layer as a porous layer arranged on a main surface of at least one side of the first solid electrolyte layer, and the third electrode is connected to the second solid electrolyte layer.
[0020] The all-solid-state sodium ion secondary battery of embodiment 9 is preferably such that, in any one of embodiments 1 to 8, the sodium ion conductive oxide contains at least one selected from the group consisting of β″-alumina, β-alumina and sodium superion conductor (NASICON) crystals.
[0021] The all-solid-state sodium ion secondary battery of aspect 10 is preferably such that, in any one of aspects 1 to 9, a ratio of the capacity of the third electrode to the capacity of the all-solid-state sodium ion secondary battery is 0.01 or more and 20 or less.
[0022] Effects of the Invention
[0023] According to the present invention, it is possible to provide an all-solid-state sodium ion secondary battery capable of improving initial charge and discharge efficiency and capacity after repeated charge and discharge. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a schematic cross-sectional view showing an all-solid-state sodium ion secondary battery according to a first embodiment of the present invention.
[0025] Figure 2 It means in Figure 1 Schematic cross-sectional view of a portion of an all-solid-state sodium-ion secondary battery provided with a solid electrolyte layer and a third electrode.
[0026] Figure 3 It means in Figure 1 A schematic cross-sectional view of a modified example of a portion of an all-solid-state sodium-ion secondary battery in which a solid electrolyte layer and a third electrode are provided.
[0027] Figure 4 This is a schematic cross-sectional view showing an all-solid-state sodium ion secondary battery according to a second embodiment of the present invention. DETAILED DESCRIPTION
[0028] Hereinafter, preferred embodiments will be described. However, the following embodiments are merely examples, and the present invention is not limited to the following embodiments. In addition, in each of the drawings, components having substantially the same function are sometimes indicated by the same reference numerals.
[0029] [First embodiment]
[0030] Figure 1 Schematic cross-sectional view showing an all-solid-state sodium ion secondary battery according to a first embodiment of the present invention. Figure 1 As shown, the all-solid-state sodium ion secondary battery 1 includes a solid electrolyte layer 2 , a positive electrode layer 3 , a negative electrode layer 4 , a first current collector layer 5 , a second current collector layer 6 and a third electrode 7 .
[0031] The solid electrolyte layer 2 has a first main surface 2a and a second main surface 2b facing each other. In addition, the solid electrolyte layer 2 has a side surface 2c connecting the first main surface 2a and the second main surface 2b.
[0032] A positive electrode layer 3 is provided on the first main surface 2a of the solid electrolyte layer 2. In the present embodiment, the positive electrode layer 3 is in contact with the solid electrolyte layer 2, and the projected area of the positive electrode layer 3 located on the solid electrolyte layer 2 when viewed from the stacking direction is smaller than the projected area of the solid electrolyte layer 2. In addition, a first collector layer 5 is provided on the main surface of the positive electrode layer 3 on the opposite side to the solid electrolyte layer 2.
[0033] A negative electrode layer 4 is provided on the second main surface 2b of the solid electrolyte layer 2. In the present embodiment, the negative electrode layer 4 is in contact with the solid electrolyte layer 2, and the projected area of the negative electrode layer 4 located on the solid electrolyte layer 2 when viewed from the stacking direction is smaller than the projected area of the solid electrolyte layer 2. In addition, the negative electrode layer 4 is provided at a position overlapping with the positive electrode layer 3 when viewed from above. Furthermore, a second current collector layer 6 is provided on the main surface of the negative electrode layer 4 on the opposite side to the solid electrolyte layer 2. In addition, the first current collector layer 5 and the second current collector layer 6 may not be provided.
[0034] The solid electrolyte layer 2 is connected to the third electrode 7. The third electrode 7 contains a metal capable of releasing sodium ions. Therefore, the third electrode 7 can also be an auxiliary electrode for replenishing sodium ions. As the third electrode 7, for example, an electrode composed of metallic sodium can be used. The third electrode 7 can also be an alloy containing metallic sodium and other metals. In addition, the third electrode 7 can also be Na2Ti3O7, Na4Ti5O 12 A substance obtained by doping sodium ions into oxide-based negative electrode active materials such as NaTi2(PO4)3, Na3Ti2(PO4)3, and Nb2O5.
[0035] Furthermore, the third electrode 7 is provided in a portion of the first main surface 2 a of the solid electrolyte layer 2 where the positive electrode layer 3 is not provided.
[0036] The all-solid-state sodium ion secondary battery 1 of the present embodiment includes the above-described structure, and thus can improve the initial charge and discharge efficiency and the capacity after repeated charge and discharge.
[0037] In the past, in a rocking chair type all-solid-state sodium ion secondary battery, when charged for the first time, sodium ions as carrier ions moved from the positive electrode layer side to the negative electrode layer side, generating a reaction in which the negative electrode active material occluded the sodium ions. However, when charged for the first time, sometimes undesirable side reactions may occur, resulting in sodium ions being captured by the negative electrode layer, and sodium ions may not be able to return to the positive electrode layer during discharge. Thus, the first irreversible capacity may be generated, and the first charge and discharge efficiency cannot be improved. In addition, in an all-solid-state sodium ion secondary battery, sometimes the capacity of the battery is reduced due to repeated charge and discharge, and the cycle characteristics are degraded.
[0038] In contrast, in the all-solid-state sodium ion secondary battery 1 of the present embodiment, the third electrode 7 that contains a metal that can release sodium ions and can replenish sodium ions is connected to the solid electrolyte layer 2, so that during the first charge and discharge, sodium ions corresponding to the portion captured by the negative electrode layer 4 and not returned to the positive electrode layer 3 can be supplied from the third electrode 7 to the positive electrode layer 3. As a result, the first irreversible capacity of the all-solid-state sodium ion secondary battery 1 can be reduced, and the first charge and discharge efficiency can be improved.
[0039] Even if the capacity of the all-solid sodium ion secondary battery 1 decreases due to repeated charge and discharge, sodium ions can be supplied from the third electrode 7 to the positive electrode layer 3. Thus, the capacity of the all-solid sodium ion secondary battery 1 after repeated charge and discharge can be increased.
[0040] In addition, in the all-solid-state sodium ion secondary battery 1 of the present embodiment, since the third electrode 7 is included, it is also possible to perform a degradation diagnosis of the battery during the first charge and discharge and after long-term cycling. For example, by comparing the electrode potentials of the positive electrode layer 3 and the negative electrode layer 4 at the initial stage of charge and discharge and after degradation, it is possible to determine whether the cause of the degradation is the positive electrode layer 3 or the negative electrode layer 4. Among them, the electrode potentials of the positive electrode layer 3 and the negative electrode layer 4 can be measured by monitoring the potential between the positive electrode layer 3-third electrode 7 or between the negative electrode layer 4-third electrode 7 using the third electrode 7. In this way, in addition to the function of supplementing sodium ions, the third electrode 7 can also function as a reference electrode.
[0041] In the past, in all-solid-state sodium ion secondary batteries, it was difficult to provide a reference electrode inside the solid electrolyte due to the use of a solid electrolyte. However, as described above, in the all-solid-state sodium ion secondary battery 1, the third electrode 7 serving as the reference electrode is connected to the solid electrolyte layer 2, so it is possible to determine whether the cause of the deterioration is the positive electrode layer 3 or the negative electrode layer 4.
[0042] In addition, when it is determined based on the results of the battery degradation diagnosis during the first charge and discharge and after long-term cycling that the capacity of either the positive electrode layer 3 or the negative electrode layer 4 has decreased, the capacity of the degraded all-solid-state sodium ion secondary battery 1 can be restored by supplying sodium ions to the positive electrode layer 3 or the negative electrode layer 4 with reduced capacity using the third electrode 7.
[0043] In the present embodiment, the ratio of the capacity of the third electrode 7 to the capacity of the all-solid-state sodium ion secondary battery 1 (third electrode / all-solid-state sodium ion secondary battery) is preferably 0.01 or more, more preferably 0.03 or more, further preferably 0.05 or more, preferably 20 or less, more preferably 10 or less, and further preferably 5 or less. When the capacity ratio (third electrode / all-solid-state sodium ion secondary battery) is above the lower limit, the effect of restoring the capacity of the all-solid-state sodium ion secondary battery 1 that has deteriorated due to repeated charge and discharge can be exerted for a longer period of time. In addition, when the capacity ratio (third electrode / all-solid-state sodium ion secondary battery) is below the upper limit, the contact between the third electrode 7 and the positive electrode layer 3 can be made more difficult to occur.
[0044] In this embodiment, the ratio (S2 / S1) of the projected area S2 of the portion of the positive electrode layer 3 disposed on the solid electrolyte layer 2 relative to the projected area S1 of the solid electrolyte layer 2 when viewed from the stacking direction is preferably 0.1 or more, more preferably 0.15 or more, preferably 0.99 or less, more preferably 0.98 or less. In this case, the battery characteristics such as the charge and discharge capacity of the all-solid-state sodium ion secondary battery 1 can be further improved.
[0045] The ratio (S3 / S1) of the projected area S3 of the portion of the solid electrolyte layer 2 provided with the third electrode 7 to the projected area S1 of the entire first main surface 2a when viewed from the stacking direction is preferably 0.01 or more, more preferably 0.03 or more, preferably 0.4 or less, more preferably 0.3 or less. In this case, the initial charge and discharge efficiency of the all-solid-state sodium ion secondary battery 1 and the capacity after repeated charge and discharge can be further improved.
[0046] In the first main surface 2a of the solid electrolyte layer 2, the ratio (S3 / S2) of the projected area S3 of the portion of the third electrode 7 disposed on the solid electrolyte layer 2 and the projected area S2 of the portion of the positive electrode layer 3 disposed on the solid electrolyte layer 2 when observed from the stacking direction is preferably 0.05 or more, more preferably 0.08 or more, preferably 0.4 or less, and more preferably 0.35 or less. In this case, the first charge and discharge efficiency of the all-solid-state sodium ion secondary battery 1 and the capacity after repeated charge and discharge can be further improved. In addition, the battery characteristics such as the charge and discharge capacity of the all-solid-state sodium ion secondary battery 1 can also be further improved.
[0047] In the present embodiment, the planar shapes of the positive electrode layer 3 , the negative electrode layer 4 , and the third electrode 7 are not particularly limited, and examples thereof include substantially rectangular, circular, and elliptical shapes.
[0048] For example, when the planar shapes of the positive electrode layer 3 and the third electrode 7 are rectangular, the extension direction (length direction) of the positive electrode layer 3 and the extension direction (length direction) of the third electrode 7 may be the same direction. In this case, the length of the positive electrode layer 3 and the length of the third electrode 7 may be the same or different. In addition, the widths of the positive electrode layer 3 and the third electrode 7 may be set so that the projected area ratio (S3 / S2) of the positive electrode layer 3 and the third electrode 7 located on the solid electrolyte layer 2 when viewed from the stacking direction is within the above range.
[0049] In addition, for example, in the case of a sulfide-based all-solid-state battery, it is necessary to integrate the negative electrode composite material layer, the solid electrolyte layer, and the positive electrode composite material layer by pressing when preparing the battery. It is difficult to make the area of the positive electrode layer and the negative electrode layer smaller than the solid electrolyte layer, and therefore it is difficult to form a third electrode on the main surface of the solid electrolyte layer.
[0050] In contrast, in the all-solid-state sodium ion secondary battery 1 of the present embodiment, for example, the positive electrode layer 3 and the negative electrode layer 4 can be formed by applying a positive electrode layer forming slurry and a negative electrode layer forming slurry on the first main surface 2a and the second main surface 2b of the solid electrolyte layer 2 and firing them. Therefore, the projected area of the positive electrode layer 3 and the negative electrode layer 4 located on the solid electrolyte layer 2 when viewed from the stacking direction can be made smaller than the projected area of the solid electrolyte layer 2. Thus, in the all-solid-state sodium ion secondary battery 1, the third electrode 7 can be formed on the first main surface 2a and the second main surface 2b of the solid electrolyte layer 2 in a portion where the positive electrode layer 3 and the negative electrode layer 4 are not provided. Among them, the structure in which the third electrode 7 is provided on the second main surface 2b of the solid electrolyte layer 2 will be described in the second embodiment.
[0051] Figure 2 It means in Figure 1 Schematic cross-sectional view of a portion of an all-solid-state sodium-ion secondary battery provided with a solid electrolyte layer and a third electrode.
[0052] like Figure 2 As shown, the solid electrolyte layer 2 includes a first solid electrolyte layer 8 and a second solid electrolyte layer 9 .
[0053] The first solid electrolyte layer 8 has a first main surface 8a and a second main surface 8b opposite to each other. A second solid electrolyte layer 9 is provided on the first main surface 8a of the first solid electrolyte layer 8. In addition, a second solid electrolyte layer 9 is also provided on the second main surface 8b of the first solid electrolyte layer 8. Thus, in the solid electrolyte layer 2, the second solid electrolyte layer 9 is provided on the main surfaces 8a and 8b on both sides of the first solid electrolyte layer 8. The first solid electrolyte layer 8 is a dense layer. In addition, the second solid electrolyte layer 9 is a porous layer. The first solid electrolyte layer 8 and the second solid electrolyte layer 9 are preferably formed as one body.
[0054] In the present embodiment, the third electrode 7 is provided on the second solid electrolyte layer 9 as a porous layer. In this case, even when the metal sodium and / or its alloy having poor adhesion to the material of the solid electrolyte layer 2 is used as the third electrode 7, the anchoring effect of the second solid electrolyte layer 9 as a porous layer can be utilized to further improve the adhesion between the third electrode 7 and the solid electrolyte layer 2. As a result, the contact resistance between the third electrode 7 and the solid electrolyte layer 2 can be reduced, the current required as the third electrode 7 can flow, and the initial charge and discharge efficiency and the capacity after repeated charge and discharge of the all-solid-state sodium ion secondary battery 1 can be further improved.
[0055] The second solid electrolyte layer 9 as a porous layer may be provided on both main surfaces 8a and 8b of the first solid electrolyte layer 8 as in the present embodiment, or may be provided only on the first main surface 8a on the side where the third electrode 7 is provided.
[0056] Figure 3 It means in Figure 1 A schematic cross-sectional view of a modified example of a portion of an all-solid-state sodium-ion secondary battery in which a solid electrolyte layer and a third electrode are provided. Figure 3 The solid electrolyte layer 2 of the modified example shown does not have a porous layer. On the other hand, a metal film 10 is provided between the first main surface 2a of the solid electrolyte layer 2 and the third electrode 7. More specifically, the third electrode 7 is provided on the first main surface 2a of the solid electrolyte layer 2 via the metal film 10. As the metal film 10, for example, an Au film or a Sn film can be used. In addition, the metal film 10 can also be formed simultaneously with the first collector layer 5.
[0057] In this way, by providing the metal film 10 between the first main surface 2a of the solid electrolyte layer 2 and the third electrode 7, the adhesion between the third electrode 7 and the solid electrolyte layer 2 can be further improved. As a result, the contact resistance between the third electrode 7 and the solid electrolyte layer 2 can be reduced, the current required as the third electrode 7 can flow, and the initial charge and discharge efficiency and the charge and discharge cycle characteristics of the all-solid-state sodium ion secondary battery 1 can be further improved.
[0058] Hereinafter, the details of each layer in the all-solid-state sodium ion secondary battery of the present invention will be described.
[0059] (Solid electrolyte layer)
[0060] The solid electrolyte constituting the solid electrolyte layer 2 is preferably formed of a sodium ion conductive oxide. As the sodium ion conductive oxide, there can be mentioned a compound containing at least one selected from Al, Y, Zr, Si and P, Na and O. As a specific example of the sodium ion conductive oxide, Beta alumina or sodium super ion conductor (NASICON) crystals with excellent sodium ion conductivity can be mentioned. Among them, the sodium ion conductive oxide is preferably at least one sodium ion conductive oxide selected from the group consisting of β″-alumina, β-alumina and sodium super ion conductor (NASICON) crystals. The sodium ion conductive oxide is more preferably β-alumina or β″-alumina. Their sodium ion conductivity is more excellent.
[0061] Beta alumina has two crystal forms: β-alumina (theoretical composition formula: Na2O·11Al2O3) and β″-alumina (theoretical composition formula: Na2O·5.3Al2O3). β″-alumina is a metastable substance, so it is usually used with Li2O or MgO added as stabilizers. Compared with β-alumina, β″-alumina has a higher sodium ion conductivity, so it is preferred to use β″-alumina alone or a mixture of β″-alumina and β-alumina, and it is more preferred to use Li2O stabilized β″-alumina (Na 1.7 Li 0.3 Al 10.7 O 17 ) or MgO stabilized β″-alumina ((Al 10.32 Mg 0.68 O 16 )(Na 1.68 O)).
[0062] As sodium superion conductor (NASICON) crystals, there are: Na3Zr2Si2PO 12 、Na 3.2 Zr 1.3 Si 2.2 P 0.8 O 10.5 、Na3Zr 1.6 Ti 0.4 Si2PO 12 、Na3Hf2Si2PO 12 、Na 3.4 Zr 0.9 Hf 1.4 Al 0.6 Si 1.2 P 1.8 O 12 、Na3Zr 1.7 Nb 0.24 Si2PO 12 、Na 3.6 Ti 0.2 Y0.8 Si 2.8 O9、Na3Zr 1.88 Y 0.12 Si2PO 12 、Na 3.12 Zr 1.88 Y 0.12 Si2PO 12 、Na 3.05 Zr2Si 2.06 P 0.95 O 12 、Na 3.4 Zr2Si 2.4 P 0.6 O 12 、Na 3.4 Zr 1.9 Zn 0.1 Si 2.4 P 0.6 O 12 、Na 3.4 Zr 1.9 Mg 0.1 Si 2.2 P 0.8 O 12 、Na 2.8 Zr2Si 2.4 P 0.6 O 12 、Na 3.6 Zr 0.13 Yb 1.67 Si 0.11 P 2.9 O 12 、Na5YSi4O 12 Among them, the preferred sodium superion conductor (NASICON) crystal is Na 3.4 Zr2Si 2.4 P 0.6 O 12 Or Na 3.05 Zr2Si 2.06 P 0.95 O 12 In this case, the sodium ion conductivity can be further improved.
[0063] The solid electrolyte layer 2 can be manufactured by mixing raw material powders, shaping the mixed raw material powders, and then firing them. For example, it can be manufactured by slurrying the raw material powders to prepare a green sheet, and then firing the green sheet. Alternatively, it can be manufactured by a sol-gel method.
[0064] The thickness of the solid electrolyte layer 2 is preferably 1 μm or more, more preferably 3 μm or more, further preferably 5 μm or more, preferably 1000 μm or less, more preferably 800 μm or less, and further preferably 500 μm or less. If the thickness of the solid electrolyte layer 2 is too thin, the mechanical strength is reduced and it is easy to break, so it is easy to cause an internal short circuit. If the thickness of the solid electrolyte layer 2 is too thick, the sodium ion conduction distance accompanying the charge and discharge becomes longer, so the internal resistance becomes higher, and the discharge capacity and the operating voltage are easily reduced. In addition, the energy density per unit volume of the all-solid-state sodium ion secondary battery 1 is also easily reduced.
[0065] As described above, solid electrolyte layer 2 may include first solid electrolyte layer 8 as a dense layer and second solid electrolyte layer 9 as a porous layer. First solid electrolyte layer 8 and second solid electrolyte layer 9 may use the same material as solid electrolyte layer 2.
[0066] The first solid electrolyte layer 8 not only has the original role of the solid electrolyte, but also functions as a base layer for ensuring the mechanical strength of the solid electrolyte layer 2. Therefore, the first solid electrolyte layer 8 has a denser structure than the second solid electrolyte layer 9.
[0067] The first solid electrolyte layer 8 preferably has a smaller porosity than the second solid electrolyte layer 9. In addition, the porosity of the first solid electrolyte layer 8 defined by the following formula (1) is preferably 20% or less, more preferably 10% or less, and further preferably 5% or less. The lower limit of the porosity is not particularly limited, and can be, for example, 0.1%.
[0068] Void ratio = (1-p / p0) × 100 (%) ... Formula (1)
[0069] In addition, in formula (1), p is the bulk density and p0 is the true density.
[0070] The thickness of the first solid electrolyte layer 8 is preferably 0.01 μm or more, more preferably 0.1 μm or more, further preferably 1 μm or more, particularly preferably 5 μm or more, preferably 300 μm or less, more preferably 200 μm or less, further preferably 150 μm or less, and particularly preferably 100 μm or less. If the thickness of the first solid electrolyte layer 8 is too small, the mechanical strength is reduced, or the positive electrode layer 3 and the negative electrode layer 4 may be short-circuited. On the other hand, if the thickness of the first solid electrolyte layer 8 is too large, the ion conductivity of the solid electrolyte layer 2 is easily reduced. In addition, there is a tendency for the energy density per unit volume of the all-solid-state sodium ion secondary battery 1 to decrease.
[0071] The second solid electrolyte layer 9 is a porous layer having voids that are three-dimensionally connected to the solid electrolyte. In addition, the positive electrode layer 3 and the negative electrode layer 4 are formed on the surface of the second solid electrolyte layer 9. At this time, the second solid electrolyte layer 9 has voids that are three-dimensionally connected, so the materials (active material powder, etc.) that constitute the positive electrode layer 3 and the negative electrode layer 4 can easily enter the voids. Thus, by providing the second solid electrolyte layer 9 as a porous layer on the first solid electrolyte layer 8 as a dense layer, the adhesion between the solid electrolyte layer 2 and the positive electrode layer 3 and the negative electrode layer 4 can be improved.
[0072] The porosity of the second solid electrolyte layer 9 defined by the above formula (1) is preferably 25% or more, more preferably 30% or more, further preferably 40% or more, preferably 97% or less, more preferably 95% or less, further preferably 90% or less. When the porosity of the second solid electrolyte layer 9 is within the above range, three-dimensionally connected voids can be more easily formed, and the adhesion between the solid electrolyte layer 2 and the positive electrode layer 3 and the negative electrode layer 4 can be further improved.
[0073] The thickness of the second solid electrolyte layer 9 is preferably 1 μm or more, more preferably 2 μm or more, further preferably 5 μm or more, particularly preferably 10 μm or more, preferably 1000 μm or less, more preferably 800 μm or less, further preferably 500 μm or less, particularly preferably 300 μm or less.
[0074] If the thickness of the second solid electrolyte layer 9 is too small, the amount of the material constituting the positive electrode layer 3 and the negative electrode layer 4 entering the voids of the second solid electrolyte layer 9 decreases, so the contact area between the solid electrolyte layer 2 and the positive electrode layer 3 and the negative electrode layer 4 decreases, and the adhesion is easily reduced. In this case, the ion conduction path at the interface between the solid electrolyte layer 2 and the positive electrode layer 3 and the negative electrode layer 4 decreases, so there is a tendency for the internal resistance of the all-solid-state sodium ion secondary battery 1 to increase. As a result, the rapid charge and discharge characteristics of the all-solid-state sodium ion secondary battery 1 are easily reduced.
[0075] The solid electrolyte layer 2 including the first solid electrolyte layer 8 as a dense layer and the second solid electrolyte layer 9 as a porous layer can be formed by, for example, the method for producing a solid electrolyte sheet described in International Publication No. 2021 / 045039.
[0076] In addition, as described above, the metal thin film 10 may be provided between the solid electrolyte layer 2 and the third electrode 7 .
[0077] For example, an Au thin film or a Sn thin film can be used as the metal thin film 10. The method for forming the metal thin film 10 is not particularly limited, and the metal thin film 10 can be formed by, for example, forming a film on the surface (first main surface 2a, etc.) of the solid electrolyte layer 2 by vapor deposition or sputtering.
[0078] The thickness of the metal film 10 is preferably 0.001 μm or more, more preferably 0.005 μm or more, further preferably 0.01 μm or more, preferably 10 μm or less, more preferably 8 μm or less, further preferably 5 μm or less. In this case, the initial charge and discharge efficiency of the all-solid-state sodium ion secondary battery 1 and the capacity after repeated charge and discharge can be improved.
[0079] (Third Electrode)
[0080] The third electrode 7 contains a metal capable of releasing sodium ions. As the third electrode 7, an electrode composed of metallic sodium can be cited. In addition, the third electrode 7 can also be an electrode composed of an alloy containing at least one metal selected from the group consisting of Sn, Ti, Bi, Au, Al, Cu, Sb and Pb and metallic sodium. As alloys containing metallic sodium, for example, Na-Au, Na-Sn, Na3Sn, NaSn3, etc. can be cited.
[0081] Among them, the reactivity of metallic sodium is high, so if it is exposed to the atmosphere, care must be taken when handling it. In contrast, in the case of alloying as in the alloy containing metallic sodium, the reactivity becomes low, so it can be handled in the atmosphere, and safety can also be improved.
[0082] The melting point of metallic sodium is 98° C., and the melting point of the alloyed metal such as the alloy containing metallic sodium is higher than 98° C. Therefore, when the third electrode 7 is composed of the alloy containing metallic sodium, it can withstand operation in a high temperature environment of 100° C. or higher.
[0083] The method for forming the third electrode 7 is not particularly limited, and can be formed, for example, by pressing a metal sodium foil onto the surface (first main surface 2a, etc.) of the solid electrolyte layer 2 by pressing or the like. The metal sodium foil can be obtained by rolling and forming the metal sodium. At this time, the pressing pressure can be, for example, 0.01 MPa or more and 1 MPa or less. In addition, the third electrode 7 can also be formed by forming a film on the surface (first main surface 2a, etc.) of the solid electrolyte layer 2 by a vapor deposition method or a sputtering method.
[0084] The thickness of the third electrode 7 is preferably 5 μm or more, more preferably 8 μm or more, further preferably 10 μm or more, preferably 2000 μm or less, more preferably 1500 μm or less, further preferably 1000 μm or less. In this case, the initial charge and discharge efficiency of the all-solid-state sodium ion secondary battery 1 and the capacity after repeated charge and discharge can be improved.
[0085] (Positive electrode layer)
[0086] The positive electrode active material contained in the positive electrode layer 3 is not particularly limited, but is preferably composed of a material having the general formula Na x M y P2O z The positive electrode active material is a crystallized glass having a crystal represented by (1≤x≤2.8, 0.95≤y≤1.6, 6.5≤z≤8, M is at least one selected from Fe, Ni, Co, Mn and Cr). Among them, the positive electrode active material having the general formula Na x A positive electrode active material composed of a crystallized glass represented by MP2O7 (1≤x≤2, M is at least one selected from Fe, Ni, Co, Mn and Cr). As such a positive electrode active material crystal, for example, Na2FeP2O7, Na2CoP2O7, Na2NiP2O7, etc. can be used.
[0087] Wherein, crystallized glass refers to the precursor glass containing amorphous phase is heated (fired) to make crystals precipitate (crystallize) and obtain. Amorphous phase can be completely transformed into crystalline phase, or residual amorphous phase can be used. In addition, one crystal can be precipitated, or more than two crystals can be precipitated. For example, crystallized glass can be judged as crystallized glass according to the peak angle given by powder X-ray diffraction (XRD).
[0088] The positive electrode layer 3 may also contain a solid electrolyte and a conductive additive. The proportions of the materials in the positive electrode layer 3 may be, for example, 30% to 95% of the positive electrode active material, 5% to 70% of the solid electrolyte, and 0% to 20% of the conductive additive in terms of mass %.
[0089] In addition, as a solid electrolyte, the solid electrolyte described in the column of solid electrolyte layer 2 can be used. As a conductive aid, for example, conductive carbon can be used. As conductive carbon, for example, acetylene black, carbon black, Ketjen black, vapor phase carbon fiber carbon conductive aid (VGCF), etc. can be cited. The conductive aid is preferably a carbon-based conductive aid composed of the above materials.
[0090] The positive electrode layer 3 can be formed, for example, by forming an electrode material layer containing a positive electrode active material precursor and, as required, a solid electrolyte powder and a conductive aid on the first main surface 2a of the solid electrolyte layer 2, and firing the electrode material layer. The electrode material layer can be obtained, for example, by applying a slurry containing a positive electrode active material precursor and, as required, a solid electrolyte powder and a conductive aid and drying it. The slurry can contain a binder, a plasticizer or a solvent as required. In addition, the electrode material layer can also be a powder compact.
[0091] The drying temperature of the slurry is not particularly limited, and can be, for example, 30° C. to 150° C. The drying time of the slurry is not particularly limited, and can be, for example, 5 minutes to 600 minutes.
[0092] The firing atmosphere is preferably a reducing atmosphere. The firing temperature (maximum temperature) can be, for example, 400° C. to 600° C., and the holding time at the temperature can be, for example, 5 minutes to less than 3 hours.
[0093] Positive electrode active material precursor:
[0094] The positive electrode active material precursor (positive electrode active material precursor powder) is preferably composed of an amorphous oxide material that can generate active material crystals by firing. When the positive electrode active material precursor powder is composed of an amorphous oxide material, active material crystals can be generated during firing, and softened and flowed to form a dense positive electrode layer 3. In addition, when the positive electrode layer 3 contains a solid electrolyte, the positive electrode active material and the solid electrolyte can also be integrated. Alternatively, when the positive electrode layer 3 is in contact with the solid electrolyte layer 2, the two can be integrated. As a result, an ion conduction path can be formed better, so it is preferred. In addition, in the present invention, "amorphous oxide material" is not limited to completely amorphous oxide materials, but also includes materials containing a portion of crystals (for example, a crystallinity of less than 10%).
[0095] In the positive electrode active material precursor powder, it is preferred to contain 25% to 55% of Na2O, 10% to 30% of Fe2O3+Cr2O3+MnO+CoO+NiO and 25% to 55% of P2O5 in terms of mole % of the following oxides. The reasons for limiting the composition are described below. In addition, in the description of the content of each component below, "%" means "mole %" unless otherwise specified.
[0096] Na2O is the general formula Na x M y P2O z (M is at least one transition metal element selected from Cr, Fe, Mn, Co and Ni, 1≤x≤2.8, 0.95≤y≤1.6, 6.5≤z≤8) The main component of the active material crystal is shown. The content of Na2O is preferably 25% to 55%, and more preferably 30% to 50%. When the content of Na2O is within the above range, the charge and discharge capacity of the all-solid-state sodium ion secondary battery 1 can be further increased.
[0097] Fe2O3, Cr2O3, MnO, CoO and NiO are also of the general formula Na x M y P2O zThe main component of the active material crystal shown. The content of Fe2O3+Cr2O3+MnO+CoO+NiO is preferably 10% to 30%, and more preferably 15% to 25%. When the content of Fe2O3+Cr2O3+MnO+CoO+NiO is above the above lower limit, the charge and discharge capacity of the all-solid-state sodium ion secondary battery 1 can be further increased. On the other hand, when the content of Fe2O3+Cr2O3+MnO+CoO+NiO is below the above upper limit, it is possible to make it difficult for undesirable crystals such as Fe2O3, Cr2O3, MnO, CoO or NiO to precipitate. In addition, in order to further improve the cycle characteristics of the all-solid-state sodium ion secondary battery 1, it is preferred to actively contain Fe2O3. The content of Fe2O3 is preferably 1% to 30%, more preferably 5% to 30%, further preferably 10% to 30%, and particularly preferably 15% to 25%. The content of each component of Cr2O3, MnO, CoO and NiO is preferably 0% to 30%, more preferably 10% to 30%, and further preferably 15% to 25%. In addition, when at least two components selected from Fe2O3, Cr2O3, MnO, CoO and NiO are contained, the total amount is preferably 10% to 30%, and more preferably 15% to 25%.
[0098] P2O5 is also a general formula Na x M y P2O z The main component of the active material crystal shown. The content of P2O5 is preferably 25% to 55%, and more preferably 30% to 50%. When the content of P2O5 is within the above range, the charge and discharge capacity of the all-solid-state sodium ion secondary battery 1 can be further increased.
[0099] In addition to the above-mentioned components, the positive electrode active material precursor powder may also contain V2O5, Nb2O5, MgO, Al2O3, TiO2, ZrO2 or Sc2O3. These components have the effect of improving electrical conductivity (electronic conductivity), and the rapid charge and discharge characteristics of the all-solid-state sodium ion secondary battery 1 are easily improved. The content of the above-mentioned components is preferably 0% to 25% in total, and more preferably 0.2% to 10%. When the content of the above-mentioned components is below the above-mentioned upper limit value, it is not easy to produce heterogeneous crystals that do not contribute to the battery characteristics, and the charge and discharge capacity of the all-solid-state sodium ion secondary battery 1 can be further increased.
[0100] In addition, the positive electrode active material precursor powder may contain SiO2, B2O3, GeO2, Ga2O3, Sb2O3 or Bi2O3 in addition to the above-mentioned components. By containing these components, the glass forming ability is further improved, and it is easy to obtain a more homogeneous positive electrode active material precursor powder. The content of the above-mentioned components is preferably 0% to 25% in total, and more preferably 0.2% to 10%. These components do not contribute to the battery characteristics, so if their content is too much, the charge and discharge capacity of the all-solid-state sodium ion secondary battery 1 tends to decrease.
[0101] The positive electrode active material precursor powder is preferably prepared by melting and molding a raw material batch. According to this preparation method, it is easy to obtain an amorphous positive electrode active material precursor powder with excellent homogeneity, so it is preferred. Specifically, the positive electrode active material precursor powder can be prepared as follows.
[0102] First, raw materials are prepared in a manner to obtain a raw material batch in a desired composition. Next, the obtained raw material batch is melted. The melting temperature can be appropriately adjusted in a manner that the raw material batch is homogeneously melted. For example, the melting temperature is preferably 800° C. or more, more preferably 900° C. or more. The upper limit of the melting temperature is not particularly limited, but if the melting temperature is too high, it will lead to energy loss, evaporation of sodium components, etc., and therefore it is preferably 1500° C. or less, more preferably 1400° C. or less.
[0103] The obtained molten material is then formed into a film by a method which is not particularly limited, for example, the molten material may be flowed between a pair of cooling rolls and formed into a film while being rapidly cooled, or the molten material may be flowed into a casting mold and formed into an ingot.
[0104] Next, the obtained compact is pulverized to obtain a positive electrode active material precursor powder. The average particle size of the positive electrode active material precursor powder is preferably 0.01 μm or more and less than 0.7 μm, more preferably 0.03 μm or more and 0.6 μm or less, further preferably 0.05 μm or more and 0.6 μm or less, and particularly preferably 0.1 μm or more and 0.5 μm or less.
[0105] Adhesives:
[0106] The binder is a material used to integrate the raw materials (raw material powders) with each other. Examples of the binder include cellulose derivatives such as carboxymethyl cellulose, hydroxypropyl methyl cellulose, hydroxypropyl cellulose, ethyl cellulose, hydroxyethyl cellulose, and hydroxymethyl cellulose, or water-soluble polymers such as polyvinyl alcohol, thermosetting polyimide, phenolic resin, epoxy resin, urea resin, melamine resin, unsaturated polyester resin, polyurethane, and other thermosetting resins, polycarbonate resins such as polypropylene carbonate, and polyvinylidene fluoride.
[0107] In addition, the thickness of the positive electrode layer 3 is preferably 10 μm or more, more preferably 50 μm or more, further preferably 100 μm or more, preferably 1000 μm or less, and more preferably 700 μm or less. When the thickness of the positive electrode layer 3 is above the above lower limit, the charge and discharge capacity of the all-solid-state sodium ion secondary battery 1 can be further improved. In addition, if the thickness of the positive electrode layer 3 is too thick, the impedance of electronic conduction becomes large, and the discharge capacity and operating voltage of the all-solid-state sodium ion secondary battery 1 may be reduced. In addition, the stress caused by shrinkage during firing becomes large, which may cause peeling.
[0108] (Negative electrode layer)
[0109] The negative electrode active material contained in the negative electrode layer 4 is not particularly limited, and for example, carbon electrode materials such as hard carbon and soft carbon can be used. The carbon electrode material is preferably hard carbon. Of course, the negative electrode active material can also include alloy-based negative electrode active materials such as tin, bismuth, lead, and phosphorus that can absorb sodium, and metallic sodium. In addition, the negative electrode layer 4 is preferably not metallic sodium or a negative electrode layer containing metallic sodium.
[0110] The negative electrode layer 4 may further include a sodium ion conductive solid electrolyte and a conductive aid. The proportion of each material in the negative electrode layer 4 may be, for example, 60% to 95% of the negative electrode active material, 5% to 35% of the sodium ion conductive solid electrolyte, and 0% to 5% of the conductive aid in terms of mass %. In addition, the sodium ion conductive solid electrolyte may use, for example, the sodium ion conductive oxide described in the column of the solid electrolyte layer 2. The conductive aid may use, for example, the conductive aid described in the column of the positive electrode layer 3.
[0111] Hereinafter, as an example, a method for forming the negative electrode layer 4 including a carbon electrode material as a negative electrode active material and a sodium ion conductive solid electrolyte will be described.
[0112] Negative electrode layer formation method:
[0113] First, prepare a slurry containing a carbon electrode material precursor and a sodium ion conductive solid electrolyte. When preparing the slurry, first, prepare a sodium ion conductive solid electrolyte precursor. In addition, at this stage, it is preferred to prepare a sodium ion conductive solid electrolyte precursor solution. Specific examples of sodium ion conductive solid electrolyte precursors and solutions thereof are described later. Furthermore, prepare a carbon electrode material precursor (a precursor of a carbon electrode material composed of hard carbon). The carbon electrode material precursor can use appropriate sugars, biomass or polymers, etc.
[0114] Next, the sodium ion conductive solid electrolyte precursor solution and the carbon electrode material precursor are mixed and then dried. Thus, a powder of a mixture of the sodium ion conductive solid electrolyte precursor and the carbon electrode material precursor is obtained. Next, the powder of the above mixture is crushed and then mixed with a conductive auxiliary agent and a binder in an organic solvent. For example, N-methyl-2-pyrrolidone can be used as the organic solvent. Thus, a slurry is obtained.
[0115] Next, the slurry is applied to the second main surface 2b of the solid electrolyte layer 2. In this way, a stacking process of stacking the solid electrolyte layer 2 and the slurry as the electrode material layer is performed. Then, the stack of the solid electrolyte layer 2 and the slurry is fired at a temperature exceeding 600°C and below 1300°C, for example, under an N2 atmosphere. In addition, the above-mentioned firing can be carried out in an inactive atmosphere. For example, the above-mentioned firing can be carried out in an Ar, Ne or He atmosphere, or it can also be carried out in a vacuum. In addition, the firing can also be carried out in a reducing atmosphere containing H2. In the case of firing in an inactive atmosphere or a reducing atmosphere, the first charge and discharge efficiency of the all-solid-state sodium ion secondary battery 1 can be further improved, so it is preferred. In addition, if the carbon electrode is not oxidized or oxidatively decomposed during firing, a small amount of oxygen may be contained in the atmosphere. The oxygen concentration can be, for example, below 1000ppm, but is not limited thereto. As described above, the negative electrode layer 4 can be prepared.
[0116] Carbon electrode material precursor:
[0117] When sugar is used as a carbon electrode material precursor, examples include sucrose, cellulose, D-glucose, sucrose, etc. When biomass is used as a carbon electrode material precursor, examples include corn stalks, sorghum stalks, pine cones, mangosteen, argan nut shells, rice husks, dandelions, cereal straw cores, ramie fibers, cotton, kelp, coconut endocarp, etc. When a polymer is used as a carbon electrode material precursor, examples include PAN (polyacrylonitrile), asphalt, PVC (polyvinyl chloride) nanofibers, polyaniline, sodium polyacrylate, tires (tire polymers), phosphorus-doped PAN, etc.
[0118] Sodium ion conductive solid electrolyte precursor and its solution:
[0119] When the sodium ion conductive solid electrolyte is beta alumina, the sodium ion conductive solid electrolyte precursor can be obtained by mixing aluminum nitrate, sodium nitrate, and lithium nitrate, for example. At this time, the ratio of each material is adjusted so as to achieve the target composition ratio of the sodium ion conductive solid electrolyte.
[0120] The sodium ion conductive solid electrolyte is sodium superion conductor (NASICON) crystal, Na5XSi4O 12In the case of a sodium ion conductive solid electrolyte precursor solution (X is at least one selected from a transition metal element of the third group, preferably a rare earth element), a solution containing sodium element, transition metal element, and carbonate ion constituting the sodium ion conductive solid electrolyte can be cited as a sodium ion conductive solid electrolyte precursor solution. In addition, in the solution, the sodium element exists in the form of sodium ions, and the transition metal element exists in the form of transition metal ions. The sodium ion conductive solid electrolyte precursor is composed of, for example, a gelled product or a dried product of the sodium ion conductive solid electrolyte precursor solution. Moreover, the above-mentioned sodium ion conductive solid electrolyte is composed of a sintered product of the sodium ion conductive solid electrolyte precursor.
[0121] In addition, in the sodium ion conductive solid electrolyte precursor solution, a solution containing nitrate ions may be used instead of carbonate ions.
[0122] In addition, in the sodium ion conductive solid electrolyte precursor solution, the carbonate ions are preferably bidentately coordinated to the transition metal element. In this case, the transition metal element is likely to exist stably in the solution.
[0123] In addition, as a counter ion of the sodium ion, it is preferable to contain NR 4+ (In the formula, each R is at least one substituent independently selected from H, CH3, C2H5 and CH2CH2OH.) In this way, the transition metal element can easily exist stably in the solution.
[0124] The sodium ion conductive solid electrolyte precursor solution can be obtained by, for example, mixing water glass (sodium silicate), sodium tripolyphosphate, and an aqueous zirconium carbonate ammonia solution.
[0125] As the binder, the binder described in the section of the positive electrode layer 3 can be used.
[0126] In addition, the thickness of the negative electrode layer 4 is preferably 0.3 μm or more, more preferably 3 μm or more, further preferably 10 μm or more, preferably 500 μm or less, and more preferably 300 μm or less. When the thickness of the negative electrode layer 4 is above the above lower limit, the charge and discharge capacity of the all-solid-state sodium ion secondary battery 1 can be further improved. On the other hand, if the thickness of the negative electrode layer 4 is too thick, the impedance of electronic conduction becomes large, and the discharge capacity and operating voltage of the all-solid-state sodium ion secondary battery 1 may be reduced.
[0127] (First current collector layer and second current collector layer)
[0128] The materials of the first collector layer 5 and the second collector layer 6 are not particularly limited, and metal materials such as aluminum, titanium, silver, copper, stainless steel or their alloys can be used respectively. The above metal materials can be used alone or in combination. Among them, their alloys refer to alloys containing at least one of the above metals. The thickness of the first collector layer 5 and the second collector layer 6 is not particularly limited, and can be 0.01 μm or more and 1000 μm or less, respectively.
[0129] The formation method of the first collector layer 5 and the second collector layer 6 is not particularly limited, and for example, physical vapor methods such as evaporation or sputtering, thermal CVD methods, MOCVD methods, chemical vapor methods such as plasma CVD methods, etc. can be cited. As other formation methods of the first collector layer 5 and the second collector layer 6, liquid phase film forming methods based on electroplating, sol-gel methods, and spin coating can be cited. However, when the first collector layer 5 and the second collector layer 6 are formed on the positive electrode layer 3 and the negative electrode layer 4 respectively by sputtering, it is preferred because of excellent adhesion.
[0130] [Second Embodiment]
[0131] Figure 4 This is a schematic cross-sectional view showing an all-solid-state sodium ion secondary battery according to a second embodiment of the present invention.
[0132] like Figure 4 As shown, in the all-solid-state sodium ion secondary battery 21, a third electrode 27 is provided on the second main surface 2b of the solid electrolyte layer 2. In addition, as for the position where the third electrode 27 is provided, it is sufficient to adopt the same position as the position where the third electrode 7 is provided in the first embodiment when viewed from above. Other aspects are also the same as the first embodiment.
[0133] The all-solid-state sodium ion secondary battery 21 also includes the third electrode 27 , and thus can improve the initial charge and discharge efficiency and the capacity after repeated charge and discharge.
[0134] Thus, in the present invention, the third electrode 7 may be provided on the first main surface 2a of the solid electrolyte layer 2, the third electrode 27 may be provided on the second main surface 2b of the solid electrolyte layer 2, or the third electrodes 7 and 27 may be provided on both the first main surface 2a and the second main surface 2b of the solid electrolyte layer 2. Alternatively, the third electrode may be provided on the side surface 2c of the solid electrolyte layer 2.
[0135] Of course, it is preferable to provide the third electrode 7 on the first main surface 2a of the solid electrolyte layer 2. In this case, the third electrode 7 can be provided on the same surface as the positive electrode layer 3. Therefore, there is an advantage that the impedance when the third electrode 7 is supplied to the sodium ions captured by the negative electrode and not returned to the positive electrode during the first charge is small compared to the case where the third electrode 7 is formed on the second main surface 2b.
[0136] Hereinafter, the present invention will be described in more detail based on specific examples, but the present invention is not limited to the following examples and can be implemented with appropriate changes within the scope of the present invention.
[0137] (Example 1)
[0138] (a) Preparation of Green Sheet for Forming First Solid Electrolyte Layer
[0139] Sodium carbonate (Na2CO3), aluminum oxide (Al2O3), magnesium oxide (MgO), zirconium oxide (ZrO2) and yttrium oxide (Y2O3) were used as raw materials. The raw material powder was prepared to have 14.2% Na2O, 75.4% Al2O3, 5.4% MgO, 4.9% ZrO2 and 0.1% Y2O3 in terms of mole %, and then fired at 1250°C for 4 hours and then pulverized in such a way that the average particle size became 2 μm. Then, 12.5 parts by mass of polyvinyl butyral resin (manufactured by Sekisui Chemical Co., Ltd., trade name "BM-SZ") as a binder was added to 100 parts by mass of the powder, and the mixture was dispersed in N-methylpyrrolidone and then fully stirred with a rotary mixer to form a slurry. The obtained slurry was applied onto a polyethylene terephthalate film (PET film) using a doctor blade, dried at 70° C., and then peeled from the PET film to obtain a green sheet for forming a first solid electrolyte layer.
[0140] (b) Preparation of Green Sheet for Second Solid Electrolyte Layer Formation
[0141] Sodium carbonate (Na2CO3), aluminum oxide (Al2O3), magnesium oxide (MgO), zirconium oxide (ZrO2) and yttrium oxide (Y2O3) were used as raw materials. The raw material powder was prepared so that Na2O was 14.2%, Al2O3 was 75.4%, MgO was 5.4%, ZrO2 was 4.9%, and Y2O3 was 0.1% in terms of mole %, and it was fired at 1250°C for 4 hours and then pulverized so that the average particle size was 2 μm. Then, 35 parts by mass of the pre-fired raw material powder and 65 parts by mass of cross-linked polymethyl methacrylate particles (manufactured by Sekisui Chemicals Co., Ltd., product number "MBX-50", average particle size 50 μm) as polymer particles were weighed and mixed. 100 parts by mass of the obtained mixture and 12.5 parts by mass of a polyvinyl butyral resin (manufactured by Sekisui Chemical Co., Ltd., trade name "BM-SZ") as a binder were weighed and dispersed in N-methylpyrrolidone, and then fully stirred with a rotary mixer to form a slurry. The obtained slurry was applied to a PET film using a doctor blade, dried at 70°C, and then peeled off from the PET film to obtain a green sheet for forming a second solid electrolyte layer.
[0142] (c) Preparation of laminate
[0143] The obtained second solid electrolyte layer forming green sheet was stacked on both main surfaces of the obtained first solid electrolyte layer forming green sheet, and isostatic pressing was performed at 90° C. and 40 MPa for 5 minutes to prepare a laminate.
[0144] (d) Firing of laminated body
[0145] The obtained laminate was fired at 1550° C. for 30 minutes to prepare a solid electrolyte layer (70 μm in thickness) in which the second solid electrolyte layer as a porous layer was provided on both main surfaces of the first solid electrolyte layer as a dense layer.
[0146] In the obtained solid electrolyte layer, the thickness of the first solid electrolyte layer was 20 μm, and the thickness of the second solid electrolyte layer was 25 μm, respectively. The porosity of the first solid electrolyte layer was 5%, and the porosity of the second solid electrolyte layer was 78%.
[0147] (e) Formation of negative electrode layer
[0148] On one main surface of the solid electrolyte layer, a negative electrode layer having a size of 20 mm square and a negative electrode active material made of hard carbon was formed. The capacity of the negative electrode layer was 2 mAh.
[0149] (f) Formation of positive electrode layer
[0150] On the other main surface of the solid electrolyte layer, a positive electrode layer having a size of 20 mm square and containing Na2FeP2O7 as a positive electrode active material was formed. The capacity of the positive electrode layer was 5 mAh.
[0151] (g) Preparation of the Third Electrode
[0152] A third electrode was prepared by attaching a φ7 mm piece of metallic sodium (weight: 10 mg) to a portion of one main surface of the solid electrolyte layer where the positive electrode layer was not formed. Thus, an all-solid-state sodium ion secondary battery was prepared. The capacity of the third electrode was 11 mAh.
[0153] (h) Charge and discharge characteristics
[0154] The all-solid-state sodium ion secondary battery was sealed with an aluminum laminate film. At this time, the tabs were drawn from the positive electrode layer, the negative electrode layer, and the third electrode. Next, the all-solid-state sodium ion secondary battery was charged and discharged under the conditions of 60°C and 0.02C. At this time, the electrode potential between the third electrode and the positive electrode layer was monitored.
[0155] Based on the above monitoring results, the generated irreversible capacity is calculated. Then, the third electrode is used as the negative electrode to discharge the positive electrode layer to replenish the irreversible capacity. At this time, the discharged capacity after replenishment is used as the first discharge capacity, and its ratio to the first charge capacity is calculated as the first charge and discharge efficiency.
[0156] Next, a charge and discharge test was repeated under the conditions of 60° C. and 0.02 C. At this time, the first discharge capacity was set as 100%, and the ratio of the discharge capacity after 50 cycles, 100 cycles, and 150 cycles was calculated.
[0157] (Example 2)
[0158] As in Example 1, an all-solid-state sodium ion secondary battery was prepared. The prepared all-solid-state sodium ion secondary battery was sealed with an aluminum laminate film. At this time, the tabs were respectively drawn from the positive electrode layer, the negative electrode layer, and the third electrode. Next, the all-solid-state sodium ion secondary battery was charged and discharged under the conditions of 60°C and 0.02C. At this time, the electrode potential between the third electrode and the positive electrode layer was monitored.
[0159] The irreversible capacity is calculated based on the monitoring results. Then, the third electrode is used as the negative electrode to discharge the positive electrode layer to replenish the irreversible capacity.
[0160] Next, the charge and discharge test was repeatedly carried out under the conditions of 60°C and 0.02C. At this time, the electrode potential between the third electrode and the positive electrode layer was monitored every 50 cycles. Based on the results of the above monitoring, the irreversible capacity generated was calculated. Then, the positive electrode layer was discharged using the third electrode as the negative electrode to replenish the irreversible capacity. Sodium ions are replenished to the positive electrode layer corresponding to the capacity portion that is reduced relative to the initial discharge capacity. At this time, the initial discharge capacity is set to 100%, and the ratio of the discharge capacity after 50 cycles, 100 cycles, and 150 cycles is calculated. In Example 2, sodium ions are replenished every 50 cycles, and accordingly, the cycle characteristics are improved compared with Example 1.
[0161] (Example 3)
[0162] When preparing the third electrode, a φ7 mm Sn / Na alloy was attached to the portion of the main surface of the solid electrolyte layer where the positive electrode layer was not formed, instead of φ7 mm of metallic sodium (weight: 10 mg), to prepare the third electrode. In other respects, an all-solid-state sodium ion secondary battery was prepared in the same manner as in Example 2, and the charge and discharge characteristics were measured. In addition, the capacity of the third electrode was 8 mAh.
[0163] (Example 4)
[0164] Using sodium carbonate (Na2CO3), yttria stabilized zirconium oxide ((ZrO2) 0.97(Y2O3) 0.03 ), silicon dioxide (SiO2), and sodium metaphosphate (NaPO3), in terms of mole%, are prepared in a manner to have a composition of 25.3% Na2O, 31.6% ZrO2, 1% Y2O3, 33.7% SiO2, and 8.4% P2O5, and are sintered at 1100°C for 8 hours and crushed. The crushed powder (average particle size: 2 μm) is used as a raw powder for the first solid electrolyte powder and the second solid electrolyte powder. Otherwise, an all-solid-state sodium ion secondary battery is prepared in the same manner as in Example 2, and the charge and discharge characteristics are measured.
[0165] (Example 5)
[0166] An all-solid-state sodium ion secondary battery was prepared in the same manner as in Example 1, except that a solid electrolyte layer consisting of β″-alumina having a thickness of 20 μm and having no porous layer was used, and the charge and discharge characteristics were measured. In addition, in Example 5, since there is no porous layer on the surface of the solid electrolyte layer, the adhesion between the third electrode and the solid electrolyte layer is low. Therefore, if sodium ions are replenished after the first discharge and every 50 cycles of charge and discharge, even if the third electrode and the positive electrode layer are energized, the resistance between the solid electrolyte layer and the third electrode is large, and the current is difficult to flow, so sodium ions cannot be supplied in the same manner as in Example 2. Therefore, in Example 5, the first charge and discharge efficiency and the charge and discharge cycle characteristics are slightly lower than those in Example 2.
[0167] (Example 6)
[0168] When preparing the third electrode, a φ7 mm Bi / Na alloy was attached to the portion of the main surface of the solid electrolyte layer on one side where the positive electrode layer was not formed, instead of φ7 mm of metallic sodium (weight: 10 mg), to prepare the third electrode. In other respects, an all-solid-state sodium ion secondary battery was prepared in the same manner as in Example 2, and the charge and discharge characteristics were measured. In addition, the capacity of the third electrode was 8 mAh.
[0169] (Example 7)
[0170] When preparing the third electrode, a φ7 mm Sb / Na alloy was attached to the portion of the main surface of the solid electrolyte layer where the positive electrode layer was not formed, instead of φ7 mm metal sodium (weight: 10 mg), to prepare the third electrode. In other respects, the all-solid-state sodium ion secondary battery was prepared in the same manner as in Example 2, and the charge and discharge characteristics were measured. In addition, the capacity of the third electrode was 8 mAh.
[0171] (Example 8)
[0172] When preparing the third electrode, a φ7 mm Sn / Na alloy was attached to the portion of the main surface of the solid electrolyte layer where the positive electrode layer was not formed, instead of φ7 mm of metallic sodium (weight: 10 mg), to prepare the third electrode. In other respects, an all-solid-state sodium ion secondary battery was prepared in the same manner as in Example 4, and the charge and discharge characteristics were measured. In addition, the capacity of the third electrode was 8 mAh.
[0173] (Example 9)
[0174] When preparing the third electrode, a φ7 mm Sn / Na alloy was attached to the portion of the main surface of the solid electrolyte layer on one side where the positive electrode layer was not formed, instead of φ7 mm of metallic sodium (weight: 10 mg), to prepare the third electrode. In other respects, an all-solid-state sodium ion secondary battery was prepared in the same manner as in Example 1, and the charge and discharge characteristics were measured. In addition, the capacity of the third electrode was 11 mAh.
[0175] (Comparative Example 1)
[0176] Except that the third electrode was not formed, an all-solid-state sodium ion secondary battery was prepared in the same manner as in Example 1, and charge and discharge measurements were performed. In Comparative Example 1, since the third electrode was not formed, sodium ions of the irreversible capacity and cycle degradation part could not be supplied to the positive electrode layer. Therefore, in Comparative Example 1, the first charge and discharge efficiency was particularly low.
[0177] The detailed results are shown in Tables 1 and 2 below.
[0178] [Table 1]
[0179]
[0180] [Table 2]
[0181]
[0182] Description of Reference Numerals
[0183] 1.21…All-solid-state sodium-ion secondary battery
[0184] 2…Solid electrolyte layer
[0185] 2a, 8a... first main surface
[0186] 2b, 8b…Second main surface
[0187] 2c…side
[0188] 3… Positive electrode layer
[0189] 4…Negative electrode layer
[0190] 5…First current collector layer
[0191] 6…Second current collector layer
[0192] 7, 27…Third electrode
[0193] 8…First solid electrolyte layer
[0194] 9…Second solid electrolyte layer
[0195] 10...Metallic film.
Claims
1. An all-solid-state sodium ion secondary battery, comprising: a solid electrolyte layer having a first main surface and a second main surface facing each other and composed of a sodium ion conductive oxide; a positive electrode layer, which is disposed on the first main surface of the solid electrolyte layer; a negative electrode layer disposed on the second main surface of the solid electrolyte layer; and The third electrode is connected to the solid electrolyte layer and includes a metal capable of releasing sodium ions.
2. The all-solid-state sodium ion secondary battery according to claim 1, wherein: The third electrode is an electrode for supplementing sodium ions.
3. The all-solid-state sodium ion secondary battery according to claim 1 or 2, wherein: The third electrode is made of metallic sodium.
4. The all-solid-state sodium ion secondary battery according to claim 1 or 2, wherein: The third electrode is composed of an alloy containing at least one metal selected from the group consisting of Sn, Ti, Bi, Au, Al, Cu, Sb, and Pb, and metallic sodium.
5. The all-solid-state sodium ion secondary battery according to claim 1 or 2, wherein: The positive electrode layer is in contact with the solid electrolyte layer, and a projected area of the positive electrode layer located on the solid electrolyte layer when viewed from the stacking direction is smaller than a projected area of the solid electrolyte layer. The third electrode is provided on a portion of the first main surface of the solid electrolyte layer that is not in contact with the positive electrode layer.
6. The all-solid-state sodium ion secondary battery according to claim 1 or 2, wherein: The solid electrolyte layer is in contact with the negative electrode layer, and a projected area of the negative electrode layer located on the solid electrolyte layer when viewed from the stacking direction is smaller than a projected area of the solid electrolyte layer. The third electrode is provided on a portion of the second main surface of the solid electrolyte layer that is not in contact with the negative electrode layer.
7. The all-solid-state sodium ion secondary battery according to claim 1 or 2, wherein: The surface layer of the solid electrolyte layer is a porous layer. The third electrode is connected to the porous layer.
8. The all-solid-state sodium ion secondary battery according to claim 1 or 2, wherein: The solid electrolyte layer has: A first solid electrolyte layer as a dense layer; and a second solid electrolyte layer as a porous layer provided on at least one main surface of the first solid electrolyte layer, The third electrode is connected to the second solid electrolyte layer.
9. The all-solid-state sodium ion secondary battery according to claim 1 or 2, wherein: The sodium ion conductive oxide contains at least one selected from the group consisting of β″-alumina, β-alumina, and sodium superion conductor crystals.
10. The all-solid-state sodium ion secondary battery according to claim 1 or 2, wherein: A ratio of the capacity of the third electrode to the capacity of the all-solid-state sodium ion secondary battery is greater than or equal to 0.01 and less than or equal to 20.
Citation Information
Patent Citations
All-solid battery
JP2010015782A